Finding Canadian polar Indigenous studies in Medline ... - Dorgan, Marlene; Campbell, Sandy; Tjosvold, Lisa; Behn-Smith, Daniele (University of Alberta Library, 2012)
The polar library community has made much progress over the past thirty years in the development of bibliographic search tools that allow fast and easy access to publications about the Arctic and Antarctic. Many of us rely heavily on tools such as Arctic and Antarctic Regions to satisfy our need for information organized with a geographic focus. For Circumpolar health researchers, there is now the growing Circumpolar Health Bibliographic Database, a subset of the Arctic Science and Technology Information System (ASTIS), which is improving access to polar health materials. However, when conducting systematic review searches, searchers are required to be as comprehensive as possible, which means that all relevant subject databases must be searched, even if overlap is substantial. As a result, Medline must be searched as part of any systematic review search related to Indigenous health issues in Canada’s Arctic regions. While the MESH Subject Headings and Geographic Headings do supply some controlled vocabulary ...